TRADISI TUBRUK BAHASA DALAM HARMONISASI SOSIAL MASYARAKAT KAMPUNG DI KABUPATEN BANYUWANGI - Ilham Nur Kholiq (IAI Darussalam, 2023)
There are two tribes in the Papring environment, namely the Madurese and Osing tribes. In everyday life, the village uses a unique language in the form of colliding or colliding, which combines Osing and Madurese languages. Language structures are a means of communication in everyday life such as in the family environment, neighborhood environment, greetings when going to work, commuting to work and the Osing Madura blend language used by all of them to understand each other. The purpose of this study is to find out the language-shaping tradition, community participation in the language-shaping tradition and the implementation of the language- shaping tradition in the social harmonization of village communities in Banyuwangi district. The method used in this study is a qualitative method with descriptive analysis techniques. The data collection techniques using observation, interviews and documentation. The tradition of language tubruk that occurs in the Osing and Madurese tribes, namely communicating in formal and non-formal situations, and these traditions arise due to side by side tribes, inter-tribal marriages, language politics in the environment and language politics in the family, the role of society in participating in the existence of language-built traditions that exist in the Paring environment in the form of establishing a traditional and cultural school then learning the local language and the implementation of language collisions that occurred between the two tribes included internal code switching, using regional language dialects.